ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA MTS - Suryanti Suryanti; Tasnim Rahmat, M. Imamuddin, Aniswita (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This research is motivated by learning mathematics, students experiencing difficulties in answering the questions given. There are still many students who do not have the courage to appear in front of the class. Many students do not believe in their abilities. The lack of students' creative thinking abilities and students' willingness to take mathematics subjects means that many students only focus on the examples that have been taught, so that when faced with different problems, students are unable to solve these problems. To solve this problem, research was carried out with the aim of revealing mathematical creative thinking abilities. The type of research used is descriptive qualitative. The instrument used is a creative thinking ability test with 2 questions. Interviews were conducted to explore students' creative thinking abilities in solving problems. The research subjects consisted of 3 students, namely 1 student in the high category, 1 student in the medium category and 1 student in the low category, and was carried out in class VII.2 MTsS Darul Makmur Sungai Cubadak. Based on the research results, it was found that overall students. Students with high abilities also have high creative thinking abilities, students with medium abilities also have sufficient creative thinking abilities, and students with low abilities also have low creative thinking abilities.